Analysis on the Determinants of Indonesia's Economic Growth within the Middle-Income Trap Perspective - Firyal, Jasmine; Fadjar, Nurman Setiawan (Journal of Development Economic and Social Studies, 2026)
Indonesia aims to achieve high-income country status by 2038, yet faces the challenge of falling into the Middle-Income Trap. Previous studies have largely used panel data approaches that cannot distinguish between short-run and long-run effects, and few have specifically examined Indonesia’s domestic innovation capacity using patent data. This study analyzes the determinants of Indonesia’s economic growth from the middle-income trap perspective, focusing on gross fixed capital formation, average years of schooling as a proxy for human capital, and the number of resident patent applications as a proxy for innovation. Using time series data from 1995 to 2024 and the error correction model, the research finds that in the long run, all three variables have a positive and significant effect on GDP per capita. In the short run, only gross fixed capital formation shows a positive and significant effect, while average years of schooling has no significant impact and patents show only weak significance. These findings imply that Indonesia needs a consistent, long-term policy strategy that balances physical investment, human capital development, and domestic innovation ecosystem strengthening to boost Indonesia’s economic growth.